STUDI KUALITATIF TENTANG PERILAKU KONSUMEN DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA PEMASARAN DIGITAL - Muhammad Kurdiyawan (Jurnal Bisnis Digital, 2026)
This study aims to analyze consumer behavior in influencing purchasing decisions in digital marketing using a qualitative approach. The research employs a descriptive case study method with data collected through in-depth interviews, observation, and documentation involving active users of digital platforms. The findings reveal that purchasing decisions are not made impulsively but through an evaluative process, including exposure to digital promotions, information search, review and rating evaluation, and consideration of price, needs, and trust in the seller. Digital marketing serves as an initial stimulus that generates purchase intention, while electronic word of mouth (e-WOM) plays a crucial role in shaping consumer perceptions and trust. In addition, influencers and social media contribute to strengthening product legitimacy. These findings indicate that purchasing decisions in digital marketing are rational and influenced by the interaction between digital stimuli and consumers’ internal processes.